Bifurcated synthesis of methylene-lactone- and methylene-lactam-fused spirolactams via electrophilic amide allylation of γ-phenylthio-functionalized γ-lactams - Sengoku, Tetsuya; Makino, Koki; Iijima, Ayumi; Inuzuka, Toshiyasu; Yoda, Hidemi (Beilstein Journal of Organic Chemistry, 2020)
New synthetic methods for spirolactams bearing an α-methylene-γ-butyrolactone or its analogous methylene-lactam have been developed. The allylation of γ-phenylthio-functionalized γ-lactams with 2-(acetoxy)methyl acrylamides was accomplished by using 2.5 equivalents of NaH to give the corresponding adducts in excellent yields. The remaining phenylthio group was substituted with a hydroxy group by treatment with CuBr, and the resulting γ-hydroxyamides were cyclized under acidic conditions to afford the corresponding methylene-lactam-fused spirolactams in high yields. On the other hand, methylene-lactone-fused spirolactams could be delivered from the allyl adducts in high yields through a sequential N-Boc protection/desulfinative lactonization.
Keywords: bifurcated synthesis; electrophilic amide allylation; α-methylene-γ-butyrolactam; α-methylene-γ-butyrolactone; spirolactams